(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2018)
Existence of miRNA binding sites in 3’-UTR, 5’-UTR and CDS regions of the mRNA of animal genes is confirmed. The efficiency of miRNA-induced repression increases with the number of sites. The binding of miRNA can be significant if the gene contains repeats of the site sequences in the coding region. It is shown that miR-1322 has polysites in CDS region of mRNAs of dozens of human genes. Experimental verification of functionality of the large number of sites is time-consuming and labor intensive. One of the ways to predict miRNA binding sites is to check the existence of these sites in mRNA of orthologous genes and to analyze their divergence during evolution. The analysis of conservation of miR-1322 polysites in CDS of mRNAs of ATN1, BCL6B, HTT, MAGI1, MLLT3, MN1, THAP11, TBP human genes and their orthologues was carried out. The studied genes are involved in development of neurodegenerative and oncological diseases. The obtained results show that polysites for binding miR-1322 are found in mRNAs of orthologous genes of many animal species. In the process of evolution, the number of binding sites changes, that indicates species dependence of efficiency of regulation of these genes expression by miR-1322. In addition to general contribution to the study of pathogenesis mechanisms caused by participation of ATN1, BCL6B, HTT, MAGI1, MLLT3, MN1, THAP11 and TBP genes our analysis allows to propose an adequate experimental animal model for further study of regulation of described genes expression by miR-1322.